Aan Widiyono KEGIATAN COOKING CLASS UNTUK MENUMBUHKAN KEMANDIRIAN DAN TANGGUNG JAWAB ANAK DI RA IMAMA MIJEN SEMARANG: KEGIATAN COOKING CLASS UNTUK MENUMBUHKAN KEMANDIRIAN DAN TANGGUNG JAWAB ANAK DI RA IMAMA MIJEN SEMARANG - Aan Widiyono (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
Cooking class activities are group activities to train creativity, share and work together. In addition, cooking classes can make children more careful and patient. This condition makes the school at RA Imama Mijen Semarang carry out routine activities every year to determine the growth and development of children in the stages of independence and responsibility. This study aims to describe the results of cooking class activities in fostering an attitude of independence and responsibility in children. This research is a quantitative descriptive study using a survey method via an online google form. The population of this study were parents of children in grade A3 at RA Imama. Cooking class activities are carried out directly at home and outside the school by taking into account the participation of parents in accompanying children's activities. The results showed that parental assistance was very influential on the independence and responsibility of children in cooking class activities, namely 93.75% more independent children, and 87.5% more responsible children. In addition, the response of parents in accompanying children in cooking class activities was in the very fun category, namely 87.5%.